Effects of Glide Path on the Centering Ability and Preparation Time of Two Reciprocating Instruments - Coelho, Marcelo Santos; Fontana, Carlos Eduardo; Kato, Augusto Shoji; de Martin, Alexandre Sigrist; Bueno, Carlos Eduardo da Silveira (Iranian Endodontic Journal, 2016)
Introduction: The aim of this in vitro study was to evaluate the effects of establishing glide path on the centering ability and preparation time of two single-file reciprocating systems in mesial root canals of mandibular molars. Methods and Materials: Sixty extracted mandibular molars with curvatures of 25-39 degrees and separate foramina for the mesiobuccal and mesiolingual canals, were divided into four groups (n=15); WaveOne+glide path; WaveOne; Reciproc+glide path and Reciproc. Non-patent canals were excluded and only one canal in each tooth was instrumented. A manual glide path was established in first and third groups with #10, 15 and 20 hand K-files. Preparation was performed with reciprocating in-and-out motion, with a 3-4 mm amplitude and slight apical pressure. Initial and final radiographs were taken to analyze the amount of dentin removed in the instrumented canals. The radiographs were superimposed with an image editing software and examined to assess discrepancies at 3-, 6- and 9-mm distances from the apex. The Kruskal-Wallis test was used for statistical analysis. The level of significance was set at 0.05. Results: Preparation in groups without glide paths was swifter than the other groups (P=0.001). However, no difference was observed regarding centering ability. Conclusion: Establishing a glide path increased the total instrumentation time for preparing curved canals with WaveOne and Reciproc instruments. Glide path had no influence on the centering ability of these systems. Keywords: Centering Ability; Glide Path; Reciproc; Root Canal Preparation; Single-File Instrumentation; WaveOne